Fungal prosthetic aortic valve endocarditis and endarteritis: An unusual cause of aortic root vegetations. Issue 2 (28th December 2018) - Carneiro, Herman; Rasalingam, Ravi
Abstract : Fungal endocarditis is a relatively rare occurrence with high morbidity and mortality. Patients may have an indolent and non‐specific course requiring a high index of suspicion to make a diagnosis. Here, we present the case of a 33‐year‐old patient who presented with fevers and acute lower limb ischemia requiring a 4‐compartment fasciotomy caused by septic emboli from Candida albicans endocarditis. The patient had a large vegetation in the ascending aorta associated with a mycotic aneurysm, which is an exceedingly rare location for a vegetation. We also review the literature and summarize the typical echocardiographic appearance and vegetation locations in fungal endocarditis.